Legal Protection for Persons with Disabilities Who Become Victims of Sexual Violence - Zahra Alsabilah; Dr. Hery Firmansyah, S.H., M.Hum., MPA (Journal of Law, Politic and Humanities, 2025)
As a human rights violation, sexual violence against persons with disabilities requires special attention from the Indonesian legal system. People with disabilities are more vulnerable to sexual violence, yet they are often overlooked in legal proceedings. This article discusses legal protection for persons with disabilities who become victims of sexual violence and the difficulties faced in enforcing their rights. This research analyzes Law No. 8 of 2016 on Persons with Disabilities and Law No. 12 of 2022 on Sexual Violence Crimes through a normative juridical approach. The results show that there are weaknesses in the legal protection process that affect victims' ability to obtain justice. Consequently, to ensure the rights of persons with disabilities are fully met, strengthening regulations and the role of law enforcement institutions in protecting persons with disabilities from sexual violence is necessary.